Emotion and aging: evidence from brain and behavior - Ebner, Natalie C.; Fischer, Håkan (Frontiers in Psychology, 2014)
Emotions play a central role in every human life from the moment we are born until we die. They prepare the body for action, highlight what should be noticed and remembered, and guide decisions and actions. As emotions are central to daily functioning, it is important to understand how aging affects perception, memory, experience, as well as regulation of emotions. The Frontiers research topic Emotion and Aging: Evidence from Brain and Behavior takes a step into uncovering emotional aging considering both brain and behavioral processes. The contributions featured in this issue adopt innovative theoretical perspectives and use novel methodological approaches to target a variety of topics that can be categorized into three overarching questions: How do cognition and emotion interact in aging in brain and behavior? What are behavioral and brain-related moderators of emotional aging? Does emotion-regulatory success as reflected in brain and behavior change with age? In this perspective paper we discuss theoretical innovation, methodological approach, and scientific advancement of the thirteen papers in the context of the broader literature on emotional aging. We conclude by reflecting on topics untouched and future directions to take.